Bringing Relationship Marketing Theory into B2B Practice: The B2B-RP Scale and the B2B-RELPERF Scorecard - Lages, Luis Filipe (2019)
This study presents a new measurement scale to assess the performance of a relationship between two firms. The Business-to-Business Relationship Performance (B2B-RP) scale is presented as a high order concept. When tested in a sample of nearly 400 SME’s purchasing managers operating in a B2B e-marketplace, our findings reveal that greater relationship performance results in better 1) relationship policies and practices, 2) relationship commitment, 3) trust in the relationship, 4) mutual cooperation, as well as 5) satisfaction with the relationship. The multi-dimensional scale shows strong evidence of reliability as well as convergent, discriminant and nomological validity. Findings also reveal that B2B relationship performance is positively and significantly associated with loyalty. While building on this scale, the authors develop the B2B-RP Scorecard intended to be included in periodic reports. At the managerial level, both the scale and the scorecard are expected to help disclose relationship performance, and act as useful instruments for periodic planning, management, controlling, and improvement of B2B relationships.